Pengaruh Kemampuan Pemahaman Konsep Matematika dan Kemampuan Numerik Terhadap Kemampuan Menyelesaikan Soal Cerita - Zulia Hartini; Syahrul Azmi; Dwi Novitasari; Nani Kurniati (Jurnal Riset Pendidikan Matematika Jakarta, 2022)
This study aims to determine the effect of the ability to understand mathematical concepts and numerical abilities on the ability to solve story problems. The study is ex-post facto with a quantitative approach. The population in this study was class VIII SMP Negeri 1 Kopang. The number of samples as many as 36 students were taken by simple random sampling technique. The data collection technique is in the form of a test. The data obtained were analyzed using a prerequisite test analysis, namely normality test, linearity test, multicollinearity test and heteroscedastic test then continued with hypothesis testing, namely simple and multiple linear regression analysis. The results of data analysis show: 1) the level of relationship between the ability to understand mathematical concepts and students' ability to solve story problems is in the very strong category because the correlation coefficient is 0.844 and there is a significant positive effect with a contribution of 71.2%; 2) the level of relationship between numerical ability and students' ability to solve story problems is in the strong category because the correlation coefficient is 0.726 and there is a significant positive effect with a contribution of 52.6%; 3) the level of relationship between the ability to understand mathematical concepts and numerical abilities with students' ability to solve story problems is in the very strong category because the correlation coefficient is 0.869 and there is a significant positive effect with a contribution of 75.6%.